The Effect of Increased Prices of Basic Materials on the Consumption of Children in Boarding Houses (Case Study of Accounting Students of Unusia 2022) - Muhammad Aras Prabowo; Sindi Prihatini; Vita Febria Mutia Zein (Trescode Green Organization, 2025)
Rising prices of basic commodities have become a major concern among Indonesians. Price spikes in basic foodstuffs such as rice, cooking oil and vegetables not only impact the macro economy but also have direct implications for the daily lives of individuals, especially boarding school children who often have to struggle with limited income to meet their daily needs. The purpose of this study is to determine whether the increase in the price of basic commodities affects the consumption of boarding students (Case Study of Students of Accounting Department Unusia 2022). In this research, the author applies the interview method, which is a communication process between the interviewer and the interviewee or participant. Interview is one of the data collection techniques commonly used in qualitative research. The results of this study indicate that price increases significantly reduce the consumption of boarding students, this means that the effect of price increases is quite large and consistent across the various samples taken, so it can be concluded that price increases do have a real and meaningful impact on the consumption of boarding students.